Alcoholic beverages, obesity, physical activity and other nutritional factors, and cancer risk: A review of the evidence. (March 2016) - Latino-Martel, Paule; Cottet, Vanessa; Druesne-Pecollo, Nathalie; Pierre, Fabrice H.F.; Touillaud, Marina; Touvier, Mathilde; Vasson, Marie-Paule; Deschasaux, Mélanie; Le Merdy, Julie; Barrandon, Emilie; Ancellin, Raphaëlle
Abstract: Purpose: Prevention is a priority in the fight against cancers, especially nutritional prevention. To update the levels of evidence of relationships between 10 nutritional factors and cancer risk, the scientific literature published from 2006 to 2014 was reviewed by an expert group. Methods: Data from 133 meta-analyses, pooled analyses or intervention trials were examined. Nearly 150 relationships between nutritional factors and cancer at various sites were evaluated. Results: According to the evidence graded as convincing or probable, these factors were divided in two groups. Factors which increase the risk of cancer are alcoholic beverages, overweight and obesity, red meat and processed meat, salt and salted foods and beta-carotene supplements. Factors which decrease the risk of cancer are physical activity, fruits and vegetables, dietary fiber, dairy products and breastfeeding. Conclusion: Three main nutritional objectives should be attained to improve cancer prevention: to reduce alcoholic beverages consumption, to have a balanced and diversified diet and to be physically active.